Komoditas Perdagangan di Pelabuhan Internasional Samudra Pasai pada Masa Dulu dan Masa Kini - Inagurasi, Libra Hari (Kapata Arkeologi, 2017)
Samudra Pasai, the first Islamic kingdom in Indonesia, its existence was influenced by the discovery of the cruise line across the shores from the Red Sea to India, the Malacca Strait to China. The kingdom is located on the edge of Malacca Strait as maritime kingdom developed as a harbor, commercial city, a heaven for traders from all over the world. The center of Samudra Pasai as a commercial city, many commodities are found. This study aims to provide an overview of the various commodities of the Samudra Pasai, through its cultural expression and identification of historical records, and its continuity in the present. Data collection is done through field observation, interview, and literature study. Archaeological, historical, and ethnographic data have been collected rather then analyzed and interpreted. This research reveals types of commodities of the Kingdom of Samudra Pasai, that is foreign commodities, local commodities, and the continuity of local commodities for export in the present. The artifacts of foreign trade commodities  are ceramics, and tombstones. Local trade commodities are pottery, salt, and pepper. Samudra Pasai pottery is allegedly made for storing containers and for dosage units of trade commodities such as pepper and salt. Pepper is a local exported commodity. The making of pottery, salt, and cultivation of pepper in the surroundings Site of the Samudra  Pasai in the present, is an economic activity that is likely to be a continuation of the earlier period, which has culture relationship since the Samudra Pasai period. Samudra Pasai, Kerajaan Islam pertama di Indonesia, keberadannya dipengaruhi oleh  penemuan  jalur pelayaran melintasi pantai-pantai dari Laut Merah hingga India, Selat Malaka hingga China. Kerajaan ini terletak di tepi Selat Malaka, bercorak  maritim, berkembang sebagai  pelabuhan, kota dagang, tempat persinggahan para pedagang dari berbagai penjuru dunia. Pusat Kota Samudra Pasai memiliki   pelabuhan dan sebagai kota dagang, banyak dijumpai berbagai komoditas. Penelitian ini bertujuan memberikan gambaran mengenai  berbagai  komoditas masa Samudra Pasai, melalui tinggalan budayanya dan identifikasi pada catatan sejarah, serta mencermati kesinambungannya pada masa kini. Pengumpulan data dilakukan melalui tahap  observasi di lapangan, wawancara, dan studi literatur. Data arkeologi, sejarah, dan etnografi yang telah terkumpul dibandingkan, dianalisis dan diinterpretasikan. Penelitian ini telah berhasil  mengungkap jenis-jenis komoditas masa Kerajaan Samudra Pasai, yakni komoditas asing, komoditas lokal, dan kesinambungannya  komoditas lokal untuk ekspor di masa kini. Artefak-artefak komoditas perdagangan asing berupa keramik, dan batu  nisan. Komoditas perdagangan lokal adalah tembikar, garam, dan lada. Tembikar Samudra Pasai diduga dibuat untuk  wadah-wadah menyimpan dan untuk satuan takaran komoditas perdagangan misalnya lada dan garam. Lada merupakan komoditas lokal yang diekspor. Pembuatan tembikar, garam, dan budi daya lada di lingkungan situs Samudra Pasai dan sekitarnya pada masa sekarang, merupakan kegiatan perekonomian, kemungkinan masih kelanjutan dari masa sebelumnya yang memiliki akar budaya sejak  pada masa Samudra Pasai.